Properties of concrete made from lightweight aggregate under different curing time - Leong Qi Wen (School of Environmental Engineering, University Malaysia Perlis, 2014)
This study aims to produce a new types of lightweight aggregate (LWA) made from foam and ordinary portland cement (OPC), obtain an optimum mix proportion for lightweight aggregate in concrete and also study compressive strength of concrete made from lightweight aggregate for different curing time.